Tingkat Kecemasan Belajar pada Peserta Didik yang Memiliki Prestasi Akademik Rendah di Kelas X SMK Negeri 4 Palembang - Wijaya, Mukti; Sofah, Rahmi; Hakim, Imron A (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2019)
The study was conducted with the aim to determine the level of learning anxiety of students who have low academic ability in class X Palembang N 4 SMK. This study uses a survey method with a quantitative approach. The population in this study were students who had low academic ability with a number of 85 and a sample or respondent of this study that was 85 students using purposive sampling. Date collection techniques use a percentage count. Aspects measured by learning anxiety in students who have low academic ability in class X of SMK N 4 Palembang, namely, physical, emotional, and mental or cognitive. The results of date analysis showed that the level of learning anxiety in students who had low academic ability in class X junior high school 4 Palembang, 35% in the very low category (SR), 49% in the low category (R),16% in the high category (T), and 0% in the very high category (ST).